Unraveling of cloud types during phases of monsoon intra‐seasonal oscillations by a Ka‐band Doppler weather radar. (4th September 2018) - Chakravarty, Kaustav; Pokhrel, Samir; Kalshetti, Mahesh; Nair, Anish Kumar Muralidharan; Kalapureddy, Madhu Chandra R.; Deshpande, Sachin M.; Das, Subrata Kumar; Pandithurai, Govindan; Goswami, Bhupendra Nath
Abstract : Ground‐based cloud radar has been used for the first time in the Indian subcontinent to explore the cloud population during the break, transition and active phases of monsoon intra‐seasonal oscillation over a region in the Western Ghats mountain. The synergetic use of in situ measurements along with the supporting large‐scale microphysical features from the reanalysis data has been utilized in order to have a closer look of the morphology of clouds along with its transition during the intra‐seasonal phases. It has been observed that the active phase is dominated by deep clouds ( 41%) along with some shallow ( 28%) and congestus clouds ( 29%) while the break phases are dominated by the shallow clouds ( 72%) during precipitating and high‐level cirrus clouds ( 65.22%) during the non‐precipitating times. The role of middle level moisture for modulating the nature of the clouds along with its role in determining the latent heating profile over the same region has also been presented. Abstract : The composite profiles of radar reflectivity as obtained from the Ka‐band Doppler weather radar for the (a) break (b) transition and (c) active phase of the study region under consideration for the year 2014.